The Shelleyan Stylistics - Muh Arif Rokhman (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1996)
Style in literature has been the most unique way of expressing the authors' ideas. It is one of the authors' identities, one that distinguishes a given author from another. Style plays a distinctive role in the language of literature. It is